Global Health - emergence, hegemonic trends and biomedical reductionism - Jens Holst (BMC, 2020)
Abstract Background Global Health has increasingly gained international visibility and prominence. First and foremost, the spread of cross-border infectious disease arouses a great deal of media and public interest, just as it drives research priorities of faculty and academic programmes. At the same time, Global Health has become a major area of philanthropic action. Despite the importance it has acquired over the last two decades, the complex collective term "Global Health" still lacks a uniform use today. Objectives The objective of this paper is to present the existing definitions of Global Health, and analyse their meaning and implications. The paper emphasises that the term "Global Health" goes beyond the territorial meaning of "global", connects local and global, and refers to an explicitly political concept. Global Health regards health as a rights-based, universal good; it takes into account social inequalities, power asymmetries, the uneven distribution of resources and governance challenges. Thus, it represents the necessary continuance of Public Health in the face of diverse and ubiquitous global challenges. A growing number of international players, however, focus on public-private partnerships and privatisation and tend to promote biomedical reductionism through predominantly technological solutions. Moreover, the predominant Global Health concept reflects the inherited hegemony of the Global North. It takes insufficient account of the global burden of disease, which is mainly characterised by non-communicable conditions, and the underlying social determinants of health. Conclusions Beyond resilience and epidemiological preparedness for preventing cross-border disease threats, Global Health must focus on the social, economic and political determinants of health. Biomedical and technocratic reductionism might be justified in times of acute health crises but entails the risk of selective access to health care. Consistent health-in-all policies are required for ensuring Health for All and sustainably reducing health inequalities within and among countries. Global Health must first and foremost pursue the enforcement of the universal right to health and contribute to overcoming global hegemony.